Publishing in the modern era - Shahid A Sami,; Fatema Jawad, (Journal of the Pakistan Medical Association, 2023)
Printed words are used to convey and conserve knowledge. The history of printing dates back to 3000 BC when documents were written on clay tablets. Other materials used were pottery imprints, wood and cloth such as silk. Printing on paper started in China in the 7th century during the Tang Dynasty which lead to the printing of books. The first printing press was created by Johannes Gutenberg from Germany in the 15th century which lead to printing of the ‘Gutenberg Bible’, opening the gateway to fast dissemination of knowledge and start of ‘Gutenberg Revolution’ with spread of the printing press and mass production of books.1 The offset printing was introduced in the late 19th century and was considered the best printing method. At the start of the 21st century, the computers further revolutionised the printing methods by replacing them with digital or electronic format. This new electronic method was a competitor for the offset printing. In developed countries, newspapers and magazines adopted the on-line digital versions for swift distribution of the material over the printed version. Comparing the two modes of publishing, the electronic form definitely offers many advantages; like ease in availability, being exceedingly visible to a large audience and user friendly links for citation.2 Journals in the e-form have more citations and particularly if open access, have a worldwide readership. Readers can provide immediate feedbacks and corrections if needed, which are easier to incorporate. The printed journals have to be purchased and physically distributed, a cumbersome process. Moreover, in printed format, any correction of errors is included in a forth coming issue as an erratum. Last decade has seen rapid transition of printed format to digital format and many journals now exist in both the forms and are steadily converting old articles as electronic archives, while others have completely phased out printed format.3 Environmental concerns of the printed media products are grave. Printing less conserves forest and natural resources. Offset printing uses chemical laden inks which release large quantities of greenhouse gasses including carbon dioxide into the atmosphere.4 The rising inflation and its impact on cost of printing cannot be ignored, especially in the developing countries. In contrast the electronic journals are gaining acceptance and popularity for being environmentally friendly and economical. Medical journals are publications which help the medical community to keep abreast with the latest research. They deliver new knowledge, foster research and disseminate information. History shows that the medical journals were published on paper as early as the 17th century and were mailed to the subscribers. The digital era with advent of portable computers and smart phones in the late 20th century, transformed the way we read medical literature today. For instance, the Journal of American Medical Association has 1.8 million subscribers linked on line every week.4 The Journal of Pakistan Medical Association (JPMA) this year completes 73 years of its purposeful life. Since its first publication in 1950, it continues to provide results of research to its worldwide readers. It is the oldest medical journal in Pakistan, and being the organ of the Pakistan Medical Association, a matter of pride for all medical professionals. To shape the future and move forward we must look back at the past. During its 73 years journey, JPMA has provided cutting edge research and high-quality contents. Launched as a quarterly publication, the journal became a monthly publication within three years and now exists in print and electronic format. It is further enriched by periodic supplements on specialised topics; thus fulfilling the appetite of its ardent readers. To keep pace with the developments in publishing, JPMA made many improvements in the past. A user friendly website was introduced with links to the latest and previous issues. The forthcoming articles can be accessed on the website by the middle of the month. Comments and appreciative remarks are received from readers residing in all countries of the world, an evidence that JPMA reach out to the medical community internationally. With a successful digital version of JPMA leading to a wider readership, the decision to discontinue the print version is being considered. JPMA will be completely digitalised which will make it environment friendly and easy to access. The digital version will increase the capacity and space for inclusion of more educational and original research articles, reviews, opinion notes, case reports, commentaries and letters to editors. As rightly quoted by Albert Einstein : ‘The measure of intelligence is the ability to change’, this change in the mode of publication will further enhance the global visibility of the journal. We hope that our readers will embrace this change and continue our patronage in the future too.